Role of tryptophan repeats and flanking amino acids in Myb-DNA interactions. - Saikumar, P (1990)
The c-myb protooncogene codes for a sequence-specific DNA-binding protein that appears to act as a transcriptional regulator and is highly conserved through evolution. The DNA-binding domain of Myb has been shown to contain three imperfectly conserved repeats of 52 amino acids that constitute the amino-terminal end. Within each repeat, there are three tryptophans that are separated by 18 or 19 amino acids and are flanked by basic amino acids. To determine the role of tryptophans and the flanking basic amino acids in the DNA-binding activity of Myb proteins, we have selectively mutagenized individual tryptophans as well as some of the amino acid residues that flank these tryptophans. Replacement of these tryptophans with glycine, proline, or arginine abolished the DNA-binding activity whereas replacement with other aromatic amino acids or leucine or alanine did not appreciably affect this activity. On the other hand the replacement of two amino acids, asparagine and lysine, that flank the last tryptophan with acidic amino acids completely abolished their DNA-binding activity. These results are consistent with a model we present in which the tryptophans form a hydrophobic scaffold that plays a crucial role in maintaining the helix-turn-helix structure of the DNA binding domain. Basic and polar amino acids adjacent to these tryptophans seem to participate directly in DNA binding.